Evaluation of ecological criteria for cotton textile products - Baydar, Gülden. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2010., 2010)
Textile industry has tremendous negative impacts on eco-system and human health and material welfare. Both cotton production which is characterized by substantial amounts of agrochemicals and water consumption and wet fabric processing leading to high resource and chemical consumption are important focus points for pollution prevention. This study aims to investigate and determine the environmental performance of both “conventional T-shirt” and “ECO T-shirt” by application of life cycle assessment (LCA) which is a comprehensive assessment methodology to evaluate the potential environmental impacts of processes, products or services on the environment. The LCA is conducted using GaBi4 software and expressed with the EDIP2003 impact assessment method. Life cycle inventory information is extracted from ecoinvent databases, combined with literature and on-site investigation of the wet processing stage improved with cleaner production (CP). The products were compared with regard to impact categories of acidification, aquatic eutrophication, terrestrial eutrophication, photochemical ozone formation and global warming. The results of the LCA study show that organic cotton cultivation has a great role on pollution prevention and use of ECO T-shirt leads to notable environmental benefits over conventional T-shirt.|Keywords: Pollution Prevention, Life Cycle Assessment (LCA), Cotton Textile Products
Keywords: Pollution prevention.; Life cycle, Human.; Cotton textiles.